O uso não autorizado de marcas de concorrentes em links patrocinados - Dourado, Maurício Custódio (2020)
The crescent and rapid development of e-commerce during the last decades and the rare specific legal studies about the matter severely hinders the comprehension about the necessity of adapting Intellectual Property Law to the new necessities imposed by the electronic mean. These difficulties are reflected on the way how legal scholarship and Courts have been resisting to recognize the legality of the non-authorized use of trademarks belonging to competitors on sponsored links services offered by search engines. However, unlikely the evolution American and European legal scholarship and Courts have undergone as time passed on, Brazil seems to be stuck on a paradigm that does not reflect the particularities of the electronic mean and tends to benefit big entrepreneurs on detriment of small ones, and to hinder consumers rights to free choice as well. On this dissertation, an analysis of the matter on all the aspects necessary to its exact understanding is proposed, defining the basic concepts of trademarks rights, of unfair competition and the grounds of e-commerce, and explaining the way how the issue has been considered in Brazil, in the United States of America and in Europe. In the end, we present our conclusions supporting the idea of inexistence of a per se illegality on the non-authorized use of trademarks by competitors on sponsored links when the way the ad is displayed suggests no existence of sponsorship between the advertiser and the trademark owner, neither provokes dilution of a notorious trademark